3-D Printing in Building Construction: A Literature Review of Opportunities and Challenges of Reducing Life Cycle Energy and Carbon of Buildings. (June 2019) - Dixit, M K
Abstract: Buildings consume approximately 48% of global energy each year as embodied and operating energy. Embodied energy is consumed in all products and processes used in building construction, maintenance, replacement, renovation and demolition. Operating energy is consumed in heating, cooling, lighting, and operating building equipment. To effectively reduce life cycle energy usage, both embodied and operating energy must be optimized. However, in spite of advancements in building envelope technologies, building systems/controls, building energy modelling, and material production, the energy and carbon footprint of buildings is still enormous. Perhaps, a new paradigm is needed to transform the way our buildings are designed and constructed. One emerging technology that could possibly help bring this paradigm shift is 3-D printing or additive manufacturing. Although, its application to mainstream construction is yet to be tested, it surely demonstrates energy and carbon benefits through innovative materials and construction processes. In this paper, we conduct a systematic review of literature to study the state of the art of 3-D printing or additive manufacturing in building construction. The goal will be to identify challenges and opportunities of saving operating and embodied energy and show future research directions to use 3-D printing technologies for energy optimization.